Recanalization Rates and Complications of Post-Endovenous Microwave Ablation in Chronic Vein Insufficiency with Large GSV Diameter - Herwirastri, Novinda; Muradi, Akhmadu (Riviera Publishing, 2025)
Endovenous Microwave Ablation (EMA) is one of the thermal ablation modalities to treat chronic venous insufficiency (CVI). The effectiveness and safety of EMAs in large-diameter saphena magna veins (GSVs) still require further research. This study aimed to compare the rates of recanalization and post-EMA complications in CVI patients with GSV diameters of <8 mm and ?8 mm. This retrospective cohort study used data from 54 patients from a multicenter (January 2023 – May 2025). Statistical analysis was performed with an unpaired t-test and a Chi-square test. The rate of venous occlusion reached 100% in both groups. The recanalization rate at 3 months post-procedure was higher in the GSV group ?8 mm (11.1%) compared to the GSV <8 mm (3.7%), although the difference was not statistically significant (p=0.299). There were no significant differences in complications of ecchymosis, thermal skin injury, and paresthesia. However, pain was reported to be significantly higher in the ?8 mm GSV group (33.3% vs 7.4%; p=0.018). The EMA is effective in achieving occlusion in a wide range of GSV diameters, but patients with a GSV of ?8 mm (especially ?10 mm) have a higher tendency to recanalize and post-procedure pain. Additional strategies are needed to be considered to increase effectiveness and comfort in the group.